Anaphylaxis following Intravenous Paracetamol: The Problem is the Solution. Issue 6 (November 2015) - Jain, S. S.; Green, S.; Rose, M.
Paracetamol is a ubiquitous analgesic and antipyretic that is widely administered, including by anaesthetists. Immediate hypersensitivity reactions to intravenous paracetamol are particularly rare. We report two cases involving four separate episodes of anaphylaxis to intravenous paracetamol in different perioperative settings without a past history of intolerance to the oral form. The allergological investigations are described, during which it became evident that both patients were allergic to an excipient (mannitol) present in the formulation and that neither was allergic to the principal agent (paracetamol). The importance of referral and investigation of perioperative drug reactions is underscored by these two cases.